2014
DOI: 10.1039/c4ra01707b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cu2ZnSnS4solar cells spray coated from a hydro-alcoholic colloid synthesized by instantaneous reaction

Abstract: A fast simple preparation based on spraying a Cu–Zn–Sn–S colloid and a sequentially annealing in N2and H2S yields compact, continuous layers with grain size of micron order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 47 publications
4
70
0
Order By: Relevance
“…As mentioned above, our standard fabrication method uses a two-step annealing process: The fi rst annealing in N 2 leads normally (0% Sn) to compact fi lms with large grains (micrometer size), but at the expense of the formation of secondary phases, as it has been shown by X-ray diffraction (XRD) and energy-dispersive X-ray microanalysis (EDX) mapping in our previous publications. [ 2,5 ] When adding Sn, the secondary phases are still present after the N 2 annealing step, as observed by XRD measurements (not shown here), the peaks of the SnS phase being particularly enhanced. Surprisingly, we observed that upon increasing the Sn content in the ink, the fi lms do not achieve full compactness after the fi rst annealing step in N 2 (see wileyonlinelibrary.com fi lms obtained from the standard ink (0% Sn added).…”
Section: Effect Of Sn Addition In the Ink Upon Thin Film Morphology Asupporting
confidence: 69%
See 4 more Smart Citations
“…As mentioned above, our standard fabrication method uses a two-step annealing process: The fi rst annealing in N 2 leads normally (0% Sn) to compact fi lms with large grains (micrometer size), but at the expense of the formation of secondary phases, as it has been shown by X-ray diffraction (XRD) and energy-dispersive X-ray microanalysis (EDX) mapping in our previous publications. [ 2,5 ] When adding Sn, the secondary phases are still present after the N 2 annealing step, as observed by XRD measurements (not shown here), the peaks of the SnS phase being particularly enhanced. Surprisingly, we observed that upon increasing the Sn content in the ink, the fi lms do not achieve full compactness after the fi rst annealing step in N 2 (see wileyonlinelibrary.com fi lms obtained from the standard ink (0% Sn added).…”
Section: Effect Of Sn Addition In the Ink Upon Thin Film Morphology Asupporting
confidence: 69%
“…[ 5 ] . The experimental details regarding the colloid synthesis, the ink preparation, and the spray deposition technique can be found in ref.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations